PAW20 Saccadic correlates of cognition in progressive supranuclear palsy. Issue 11 (22nd October 2010) - Ghosh, B; Rowe, J B; Carpenter, R H S; Calder, A J; Peers, P V; Lawrence, A D; Hodges, J R
Abstract : Introduction: Oculomotor and cognitive functions are both affected by progressive supranuclear palsy (PSP). From functional-anatomical models of parallel cortico-subcortical loops, we predicted that cognition and oculomotor control would be more closely related than motor performance. Methods: 19 PSP patients and 22 controls underwent reflex saccade monitoring with a head mounted infrared saccadometer and the LATER model of reciprocal latency (Ober consulting; Carpenter et al 1995). Cognitive assessment included: the Addenbrookes Cognitive Assessment-revised (ACE-R); Hayling & Brixton Tests; frontal assessment battery (FAB) and tests of social cognition using: emotion recognition tests; TASIT and Mind in the Eyes tests. Stepwise regression analyses of cognitive function (ACE-R) included reciprocal latency, UPDRS and disease duration. Results: Saccadometry was well tolerated. PSP increased saccade latency. Reciprocal latency correlated with cognitive function (ACE-R; errors on the Hayling; FAB; face emotion recognition and TASIT). In stepwise regression analyses, reciprocal latency was the best predictor for cognition. In the presence of reciprocal latency, UPDRS and disease duration did not significantly predict cognitive function. Conclusion: PSP increased reflex saccadic latency. Critically, reciprocal latency correlated with cognitive ability, beyond UPDRS and disease duration. In the future, latencies may be able to be used as an objective correlate of cognition in this patient group.